Information processing in decisions under risk: evidence for compensatory strategies based on automatic processes - Andreas Glöckner; Ann-Katrin Herbold (Max Planck Institute for Research on Collective Goods, 2008)
Many everyday decisions have to be made under risk and can be interpreted as choices between gambles with different outcomes that are realized with specific probabilities. The underlying cognitive processes were investigated by testing six sets of hypotheses concerning choices, decision times, and information search derived from cumulative prospect theory, decision field theory, priority heuristic and parallel constraint satisfaction models. Our participants completed forty decision tasks of two gambles with two non-negative outcomes each. Information search was recorded using eye-tracking technology. Results for all dependent measures conflict with the prediction of the non-compensatory priority heuristic and indicate that individuals use compensatory strategies. Choice proportions are well predicted by a cumulative prospect theory. Process measures, however, indicate that individuals do not rely on deliberate calculations of weighted sums. Information integration processes seem to be better explained by models that partially rely on automatic processes such as decision field theory or parallel constraint satisfaction models.
Keywords: 330; Risky Decisions; Cumulative Prospect Theory; Decision Field Theory; Priority Heuristic; Parallel Constraint Satisfaction; Eye Tracking; Intuition; Entscheidung bei Risiko; Informationsverhalten; Kognition; Test